Sustainable earnings: How can herd-behaviour on financial accumulation feed into a resilient economic system? - Aurelie Charles; Damiano Sguotti (Luxembourg Income Study (LIS), 2021)
The paper applies a methodological tool able to frame national policies with sustainable financial flows between social groups. In effect, exchange-entitlement mapping (e-mapping) shows the interdependency of capital and labour earnings across social groups, which is then accounted for in the policy planning of future financial flows for the green transition. First, the paper highlights the extent to which herd-behaviour feeds into capital and labour earnings by social, occupational, demographic, and regional groups for the UK, France, and Italy over the past forty years. Second, learning from these past trends, the paper proposes a policy framing of 'sustainable earning trends' to hamper or facilitate financial flows towards sectors, occupations, and regions prone to herd-behaviour. The paper concludes that for an economic system to be resilient, it should be able to recycle external shocks on group earnings into economic opportunities for the green transition.
Keywords: 330; group behavior; financial accumulation; earnings